Managing up : how to move up, win at work, and succeed with any type of boss - Abbajay, Mary, 1964- (Gildan, 2018)
Managing Up is your guide to the most valuable 'soft skill' your career has ever seen. It's not about sucking up or brown-nosing; it's about figuring out who you are, who your boss is, and finding where you meet. It's about building real relationships with people who have influence over your career.